PREVALENCE OF DENTAL CARIES AMONG ADOLESCENT STUDENTS. - Sher Muhammad Chandio1 , Atta Muhammad Chandio2 , Jawaid Hussain Lighari3 , Imran Ali Jamali4 , Zenab Shumaila5 , Wasim Akram6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: Dental caries is an irreversible microbial disease of calcified tissues of teeth. Despite numerous scientific progressions, it continues to be the focal public health problem, particularly in developing countries. In 2016 it was leading disease affecting 2.4 billion people globally. The disease is of concerned severe in adolescents, but no such studies have been conducted in Pakistan, which involves the entire period of adolescence. METHODS: It was a school-based cross-sectional study conducted from 19th September 2019 to 19th February 2020. The sample size consists of 350 school students aged between 12-18 years from Private and government schools of Shaheed Benazirabad. An intraoral examination was performed by the researcher himself under strict protocol. DMFT scale was used to assess and measure dental caries. Data was analyzed through SPSS v25. Statistical association with age, gender and type of school was confirmed by chi-square test, independent sample t-test and bivariate analysis. RESULTS: Overall prevalence of dental caries was 72% with mean DMFT 3.28±3.05. Prevalence was high 89.2%in 18 years old students, 76.7% in boys and 77% in government schools. Statistical analysis showed a significant association with age, gender and type of school. CONCLUSION: Dental caries is a significant threat to the health of adolescents. Robust preventive strategies incorporating health education, school health services and legislation should be adopted to overcome the problem.